Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing pada Pembelajaran Biologi Siswa Kelas XI - Adelia Adelia; Sepriyaningsih Sepriyaningsih; Reny Dwi Riastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop valid, practical, and effective Student Worksheet (LKPD) teaching materials for Biology Learning for Grade XI Students of Muara Lakitan State Senior High School. This research is a Research and Development study using the ADDIE model. Based on the validation analysis of the guided inquiry-based LKPD teaching materials using a five-point scale calculation, the language validator scored 27 (high), the media validator scored 29 (high), and the material validator scored 28 (high). The analysis of the teacher and student practicality sheet assessments met the practical criteria with an average score of 90.31%, categorized as very practical. The effectiveness assessment analysis obtained an average N-Gain score of 0.77, categorized as high. Based on the results of the study, it can be concluded that the Guided Inquiry-Based Student Worksheet (LKPD) teaching materials for Biology Learning for Grade XI Students of Muara Lakitan State Senior High School are proven to be valid, practical, and effective, making them suitable for use in Biology learning for Grade XI Students of Muara Lakitan State Senior High School. Keywords: Biology, LKPD, Development, Senior High School